2011
DOI: 10.3390/agriculture1010022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage and Crop Residue Application on Soybean Nitrogen Fixation in a Tropical Ferralsol

Abstract: This study was aimed at quantifying soybean (Glycine max) nitrogen fixation under reduced tillage (RT) and conventional tillage (CT) in a tropical Ferralsol of the sub-humid zone of western Kenya, using the isotope 15 N dilution method. Crop residue (CR) management was a superimposed treatment in soybean-maize rotation and intercropping systems. This study quantified N in abscised soybean leaves. Soybean-N derived from the atmosphere (%NDfA) ranged between 41-65%; it was higher (P < 0.05) in RT (55.6%) than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
7
18
1
Order By: Relevance
“…The study findings are supported by [9] who demonstrated the contribution of soybean litter to soil N buildup. The findings are further in agreement with the findings of [27] who reported an increase in NO 3 -N with residues incorporated and N application at 40 kg ha -1 .…”
Section: Accumulation Of Soil No 3 -N As Influenced By Soybean Residusupporting
confidence: 78%
See 1 more Smart Citation
“…The study findings are supported by [9] who demonstrated the contribution of soybean litter to soil N buildup. The findings are further in agreement with the findings of [27] who reported an increase in NO 3 -N with residues incorporated and N application at 40 kg ha -1 .…”
Section: Accumulation Of Soil No 3 -N As Influenced By Soybean Residusupporting
confidence: 78%
“…For example, hairy vetch (Vicia villosa), and crimson clover (Trifolium incarnatum,) were found to contribute 204 kg ha -1 and 163 kg ha -1 respectively [8]. Other researchers [9] showed that soybean litter fall over the growing period of the crop contributed 8.2 to 11.8 kg N ha -1 from N fixation while residues returned to the field after harvest had total N content of up to 30 kg N ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Under conventional tillage, the plots were prepared by hand hoeing to approximately 15 cm soil depth, mimicking practices used by smallholder farmers in this region (Kihara et al 2011). Weeding was performed by hand hoe to 8 cm depth thrice per season.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Previous studies have found a promotion of nodulation under no-tillage systems and that there was a close positive relationship between nodule number and the N-content of roots within conservation tillage systems (Hughes and Herridge, 1989;Sidiras et al, 1999;Kihara et al, 2011;Ló pez-Bellido et al, 2011). Tillage system in the current case study had no effect on nodule number but did significantly influence nodule surface area (a surrogate for overall nodule size).…”
Section: Discussionmentioning
confidence: 56%
“…These factors include: soil temperature; water availability; soil acidity; soil salinity; intercropping; crop rotation; fertilization regime; inoculation practices; and tillage practices (Sprent, 1972;Hungria and Vargas, 2000;van Kessel and Hartley, 2000;ElAkhal et al, 2013). Reduced tillage and cover crops prior to a legume crop often increase nodulation, as is the case for soybean nodulation (Hughes and Herridge, 1989) and rates of N fixation (Kihara et al, 2011) for this crop. Increased N fixation has also been noted under reduced tillage for chickpea and faba bean (Vicia faba L.; Ló pez-Bellido et al, 2011).…”
mentioning
confidence: 99%